2011
DOI: 10.1007/s00066-011-0018-7
|View full text |Cite
|
Sign up to set email alerts
|

Relocatable fixation systems in intracranial stereotactic radiotherapy

Abstract: The mask fixation system in conjunction with a bite-block is the most accurate fixation for SCRT reducing craniocaudal and rotational movements. Patients favoured the more comfortable but less accurate neck support. To optimize the accuracy of SCRT, additional regular portal imaging is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Theelen et al . recently provided a comprehensive tabular summary of previously published studies involving thermoplastic masks with an additional dental tray: most series found an accuracy of <2 mm [12]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theelen et al . recently provided a comprehensive tabular summary of previously published studies involving thermoplastic masks with an additional dental tray: most series found an accuracy of <2 mm [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Such studies are difficult to compare due to the employment of different methods and measurement of deviations. Despite the advantages advocated by the authors most of them seem equally effective, with reported daily setup errors ranging between 0.5–1 mm in the best series [12]. …”
Section: Introductionmentioning
confidence: 99%
“…While there exist a number of studies that have assessed the positional accuracy and stability of different invasive and noninvasive immobilization systems for cranial stereotactic radiotherapy,6, 9, 16, 17, 18, 19, 20 to our knowledge, no study has directly compared the performance of various systems used in the same institution.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, stereotactically guided treatments using linear accelerator (LINAC)-based stereotactically based or frameless radiosurgery treatments are available. From the clinical perspective in the case of skull base meningiomas, all approaches have the potential to create comparable dose distributions with respect to dose conformity and sparing of normal tissue, therefore leading to comparable short-term clinical outcomes [11-13]. It is important to remember however that physicians do not all use these techniques similarly.…”
Section: Radiosurgery and Fractionated Radiation Therapymentioning
confidence: 99%